STANDARISASI SIMPLISIA DAUN TEMPUYUNG (SONCHI FOLIUM) HASIL BUDIDAYA di UBAYA TRAINING CENTER TRAWAS MOJOKERTO - Nikmatul Ikhrom Eka Jayani; Helena Oktaviani Handojo (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2021)
The objective of this research was to determine the specific, non specific parameter and total flavonoid content of dried Sonchi Folium, which are cultivated from the UTC (Ubaya Training Center), Trawas, Mojokerto. Crude material herbal Sonchi Folium was successfully prepared by collecting, wet sorting, washing, cutting and dry sorting. Dried Sonchi Folium were treated as chooped, crude drug powder. Specific and non specific parameter of Sonchi Folium standardization based on (MMI) Materia Medica Indonesia. Specific parameters test including macroscopic and microscopic properties of Sonchi Folium meet a criteria of MMI. The total flavonoid in ethanolic extract with AlCl3 methods was 1,38% QE (Quercetin equivalent). Non-specific parameters test resulted in the loss on drying 11,23% (standart <10%), total ash content 19,42% (standart <17%), acid insoluble ash content 0,58% (standart <0.25%), water soluble content 20,04% (standart >17.1%) and ethanol soluble content 6,44% (standart > 7.5%), only water soluble content meet a standart criteria.